Store-specific grocery shopping patterns and their association with objective and perceived retail food environments - Daisy Recchia; Marlène Perignon; Pascaline Rollet; Nicolas Bricas; Simon Vonthron; Coline Perrin; Lucie Sirieix; Hélène Charreire; Caroline Méjean; Surfood-Foodscapes Working Group (Cambridge University Press, 2024)
Abstract Objective: To explore store-specific grocery shopping patterns and assess associations with the objective and perceived retail food environment (RFE). Design: This cross-sectional study used principal component analysis and hierarchical cluster analysis to identify grocery shopping patterns and logistic regression models to assess their associations with the RFE, while adjusting for household characteristics. Setting: The Montpellier Metropolitan Area, France. Participants: To be eligible for inclusion, participants had to be 18 years of age or older and reside in the Montpellier Metropolitan Area. Analyses were carried out on 415 households. Results: Households of cluster 'Supermarket' (49 % of households) primarily shopped at supermarkets and were less likely to live near a convenience store. Households of cluster 'Diversified' (18 %) shopped mostly at organic stores, at markets, at specialised stores, and from producers and were more likely to have a market in their activity space. Households of cluster 'Discount' (12 %) primarily shopped at discounters and were less likely to perceive a producer in their activity space. Households of cluster 'Convenience' (12 %) mostly shopped online or in convenience stores. Finally, households of cluster 'Specialized' (9 %) had high expenditures in greengrocers and in other specialised food stores and were more likely to live near a specialised food store. Conclusions: This study highlighted the importance of considering both perceived and objective RFE indicators, as well as assessments around the home and in activity space. Understanding how people buy food and interact with their RFE is crucial for policymakers seeking to improve urban food policies.